2014
DOI: 10.1364/oe.22.025679
|View full text |Cite
|
Sign up to set email alerts
|

Mutual conversion and asymmetric transmission of linearly polarized light in bilayered chiral metamaterial

Abstract: We propose a kind of planar chiral optical metamaterial consisting of two layers of connected I-shape resonators arranged by a twist angle of 90°. Numerical simulation results demonstrate that our scheme can realize a mutual polarization conversion and dual-band asymmetric transmission for linearly polarized waves in the optical regime. For the forward propagation, the x-to-y and y-to-x polarization conversions in the proposed bilayered metamaterial result from the concentric and eccentric C-shaped dimers, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…Controlling this plasmon excitation of metasurfaces actively will enable dynamic tunability of the asymmetric transmission and potentially expand the range of asymmetric transmission applications even further. However, the tunability of the plasmon excitation in metasurfaces has to be controlled by accurately fabricating different nanostructures in the previous works, which is an inherent drawback [14,16,17]. Moreover, the proposed asymmetric transmission devices always have complex structures which prevent its real applications in modern optical systems.…”
mentioning
confidence: 99%
“…Controlling this plasmon excitation of metasurfaces actively will enable dynamic tunability of the asymmetric transmission and potentially expand the range of asymmetric transmission applications even further. However, the tunability of the plasmon excitation in metasurfaces has to be controlled by accurately fabricating different nanostructures in the previous works, which is an inherent drawback [14,16,17]. Moreover, the proposed asymmetric transmission devices always have complex structures which prevent its real applications in modern optical systems.…”
mentioning
confidence: 99%
“…Many new properties have been found in the chiral metamaterials, such as asymmetric transmission (AT), circular dichroism and optical activity. Asymmetric transmission, dened as the difference between the transmittance in two opposite propagation directions, has been largely reported on planar metasurfaces in microwave, [5][6][7][8][9][10][11][12] THz, 13-20 infrared 21 and optical [22][23][24][25][26][27][28] regimes. It was found that a chiral metamaterial with symmetry breaking can exhibit an AT effect for linear and circular polarizations.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] A way to enhance chiraldependent effects in the subwavelength structures is to construct quasi-2D planar chiral metamaterials with the layered metallic patterns. [13][14][15] The production of such structures is well developed and is usually realized by circuit-board printing technology in microwave band [16][17][18][19][20] or by standard micro-and nanolithography techniques for higher frequencies. 21,22 However, there is a limitation related to their electromagnetic properties considering that a complete asymmetric transmission is a resonant feature strongly dependent on dissipation.…”
Section: Introductionmentioning
confidence: 99%